Imperial Overstretch: Germany in Soviet Policy from Stalin to Gorbachev An Analysis Based on New Archival Evidence, Memoirs, and Interviews - Adomeit, Hannes (Internationale Politik und Sicherheit, 2016)
This book focuses on the dynamics which led to the division of Germany - a process that occurred by default rather than design; the role played in that process by the Soviet Union under Stalin; the reasons why his successors, from Khrushchev to the Communist Party general secretaries Brezhnev, Andropov and Chernenko, stubbornly clung to the division of Germany for almost half a century; their increasing realisation of the 'costs of an empire'; the failure of their attempts to stop East Germany's increasing dependence on West Germany; and, finally, the reasons why Gorbachev accepted the dissolution of the Soviet empire, abandoned his 'strategic ally' and consented to the unified Germany's membership of NATO. The Soviet Union, the book concludes, had overextended itself in its attempt to maintain imperial control by the constant application of 'hard power'. The lesson for today is obvious, but Putin appears set to repeat the fateful course pursued by his Soviet predecessors.